Characteristics of open globe injury in children under six - Li, Rui; Qi, Shounan; Zhang, Ying; Wang, Chenguang (Frontiers in Pediatrics, 2024)
Introduction: This study aimed to analyse the clinical characteristics of open globe injury (OGI) in children under six. Methods: A retrospective analysis was conducted on the medical data of children with OGI admitted to the Eye Center of the Second Hospital of Jilin University, China, between 1 January 2012 and 31 December 2020. Results: The study included 106 children, with 61 males (57.5%) and 45 females (42.5%), and the mean age was 4.14 ± 1.58 years. Injuries predominantly affected the right eye (53.8%). Sharp objects were the leading cause of injuries (56.6%). Most wounds (91.5%) occurred in zone I, and penetrating trauma was the most common injury type (64.2%). The concomitant OGI findings included traumatic cataracts (47.2%), iris prolapse (53.8%), endophthalmitis (22.4%), vitreous prolapse (17.0%), retinal detachment (5.7%), eyelid laceration (7.5%), and orbital fractures (1.9%). Univariate analysis showed that wooden materials (p = 0.045), needles (p = 0.045), postinjury admission time (p < 0.001), injury zone (p = 0.025), and iris prolapse (p = 0.022) were significantly associated with endophthalmitis. Multivariate logistic regression analysis revealed that delayed admission for ≥24 hours was an independent risk factor for endophthalmitis (p = 0.007). Preoperative and postoperative visual acuities were significantly correlated (p < 0.001). Conclusions: OGIs are more common in males under six years old, with sharp objects being the primary cause. Prompt surgical intervention can lower the risk of endophthalmitis. Increased awareness of the severity of OGI and understanding the risk factors for endophthalmitis will aid in developing effective strategies to minimise ocular complications.